Effect of SULT2B1 genetic polymorphisms on the sulfation of dehydroepiandrosterone and pregnenolone by SULT2B1b allozymes. (1st October 2019) - Alherz, Fatemah A.; El Daibani, Amal A.; Abunnaja, Maryam S.; Bairam, Ahsan F.; Rasool, Mohammed I.; Sakakibara, Yoichi; Suiko, Masahito; Kurogi, Katsuhisa; Liu, Ming-Cheh
Abstract: Pregnenolone and dehydroepiandrosterone (DHEA) are hydroxysteroids that serve as biosynthetic precursors for steroid hormones in human body. SULT2B1b has been reported to be critically involved in the sulfation of pregnenolone and DHEA, particularly in the sex steroid-responsive tissues. The current study was designed to investigate the impact of the genetic polymorphisms of SULT2B1 on the sulfation of DHEA and pregnenolone by SULT2B1b allozymes. Ten SULT2B1b allozymes previously prepared were shown to exhibit differential sulfating activities toward DHEA and pregnenolone in comparison to the wild-type enzyme. Kinetic studies revealed further significant changes in their substrate-binding affinity and catalytic activity toward DHEA and pregnenolone. Taken together, these results indicated clearly a profound effect of SULT2B1 genetic polymorphisms on the sulfating activity of SULT2B1b allozymes toward DHEA and pregnenolone, which may have implications in inter-individual variations in the homeostasis of these two important steroid precursors. Highlights: Ten SULT2B1b allozymes were bacterially expressed and affinity-purified. Pregnenolone and dehydroepiandrosterone sulfating activities of SULT2B1b allozymes were analyzed. Kinetic constants of SULT2B1b allozymes in the sulfation of pregnenolone or dehydroepiandrosterone were determined.